Decision-Making on a National Home Improvement Programme in Sweden and Its Effects on the Built Environment, 1984–1993. (3rd April 2019) - Tunefalk, Martin; Legnér, Mattias
ABSTRACT: Following a period of unprecedented building in the 1960s and 1970s, the national government of Sweden decided on a programme to promote renovations, refurbishments and extension of older buildings. The programme (abbreviated R.O.T.) was introduced in 1984 and consisted of loans and subsidies for the modernisation of houses older than 30 years, as well as information to home owners and builders on the benefits of home improvement. The target was to modernise 425, 000 homes during the period 1984–1993. The programme stated that 'the energy-saving measures must be intensified' and 'all out-dated and the main part of all inadequate apartments should be rebuilt to modern apartments, or be demolished'. By relating the processes that formed R.O.T. to theories of decision-making, this study contributes to a better understanding of how housing policies may affect historical values in the built environment. The study reveals a conflict of interest between stakeholders. R.O.T. developed ad hoc as discourses shifted between interests. Initially, it was presented as a solution for unemployment in the building sector and a social improvement for the poor and elderly. It was not until the late 1980s that a discussion turned to the consequences for historical values.